TRANSFORMATIONAL LEADERSHIP OF HUGHIE CAMPBELL CHARACTER IN THE MOVIE THE BOYS - Ramadhan, Dani (J-MIND (Jurnal Manajemen Indonesia), 2024)
Leadership is an important element in every organization, including the one featured in the movie. This research aims to analyze the character of Hughie Campbell in the The Boys series through the perspective of transformational leadership. The purpose of this research is to show the character of Hughie, despite not having superpowers, able to display strong leadership characteristics and influence his his peers. This research uses a case study approach and descriptive method to delve deeper into the transformational leadership characteristics possessed by Hughie, such as idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The results showed that Hughie was able to influence his colleagues through strong moral principles, providing inspiration in difficult situations, and encouraging his team to think critically. difficult situations, and encouraging his team to think critically in the face of challenges. In addition, he also paid attention to the well-being of individuals in the team, which created a closer working relationship. closer working relationships. This study concludes that transformational leadership theory is relevant to analyze in a fictional context and has real implications in understanding leadership in the real world. leadership in the real world.